Study on the Characteristics of Natural Fibre Composite Using Coir Fibre Composite for Car Outer Hood - Danny Iskandar Mohd Yazli,; Norhasikin Ismail, (Progress in Engineering Application and Technology, 2024)
The use of natural fiber composites in automotive applications has gained significant attention in recent years due to their potential to reduce the environmental impact of vehicles. Coir fiber, derived from coconut husk, has emerged as a promising natural fiber for composite materials. This research presents a comprehensive analysis of the characteristics and performance of natural fiber composites using coir fiber, specifically for the outer hood of a car. Different fibre to weight ratios (wt%) of coir fibre were use which are 10 %, 15 % and 20 % and mixed with epoxy resin and epoxy hardener to create the coir fibre composite. The original state of coir fibres were brown and matured coconut husks. The coir fibres was extracted by using a fibre extractor machine and then undergoes with alkaline treatment which is made of 10 Litres of distilled water and 180 g of NaOH for 42 hours before being rinsed with distilled water containing a few drops of acetic acid and being oven dried at 60 ᵒC for 72 hours. Lastly it was grinded using a RT-34 Vertical High Speed Pulverizing Machine to have the fibre length at 0.1 to 0.2 mm. Hand lay-up method was used on a 20 cm x 20 cm mould to create a square shaped coir fibre composite than was cut into the specific ASTM for each test. The mechanical test conducted was tensile strength test (ASTM D638 type 4), bending test (ASTM D790) and impact test (ASTM D256). The results from the tensile strength test shows that the highest obtain was 15.7 MPa from the 10 wt% and the young modulus of 8.52 MPa. The bending test shows the highest is the 20 wt% which is 122.96 MPa. The highest result for impact test was at 15 wt% with having the impact energy for dual unit of 5.87 MPa and 82.92 J/m, and the energy absorption of 0.71 %. It can be concluded that the 20 wt% of coir fibre was the most optimum mixture to be used for the outer hood application.